2007
DOI: 10.1042/bc20070058
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a bipartite focal adhesion localization signal in RhoU/Wrch‐1, a Rho family GTPase that regulates cell adhesion and migration

Abstract: Background information. Rho GTPases are important regulators of cytoskeleton dynamics and cell adhesion. RhoU/ Wrch-1 is a Rho GTPase which shares sequence similarities with Rac1 and Cdc42 (cell division cycle 42), but has also extended N-and C-terminal domains. The N-terminal extension promotes binding to SH3 (Src homology 3)-domain-containing adaptors, whereas the C-terminal extension mediates membrane targeting through palmitoylation of its non-conventional CAAX box. RhoU/Wrch-1 possesses transforming activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
81
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 57 publications
(90 citation statements)
references
References 59 publications
8
81
1
Order By: Relevance
“…In these cells, RhoU induces Pyk2-and Src-dependent stress fiber dissolution. RhoU binding to Pyk2 requires its proline rich region, but similarly to what we found (Ory et al, 2007), RhoU-dependent effects on the actin cytoskeleton also requires an intact effector binding site (Ruusala and Aspentröm, 2007).…”
Section: Interestingly Recent Findings Have Reported a Src-dependentsupporting
confidence: 80%
See 3 more Smart Citations
“…In these cells, RhoU induces Pyk2-and Src-dependent stress fiber dissolution. RhoU binding to Pyk2 requires its proline rich region, but similarly to what we found (Ory et al, 2007), RhoU-dependent effects on the actin cytoskeleton also requires an intact effector binding site (Ruusala and Aspentröm, 2007).…”
Section: Interestingly Recent Findings Have Reported a Src-dependentsupporting
confidence: 80%
“…This localization is dependent on the ability of RhoU to bind to effectors since a RhoU mutant unable to bind the Cdc42/Rac interaction domain of PAK is only found on vesicles (Ory et al, 2007;HB, unpublished data). Like many components of podosomes, RhoU is also found in focal 8 adhesions where it alters their dynamics and, in consequence, the migration rate of fibroblasts (Ory et al, 2007;Chuang et al, 2007). The C-terminal extension of RhoU and residues critical for effector binding are required for targeting RhoU to focal adhesions (Ory et al, 2007).…”
Section: What Else Beyond Rhoa Rac1 and Cdc42 In Osteoclasts?mentioning
confidence: 95%
See 2 more Smart Citations
“…We previously showed that Wrch1 associated with adhesion structures: it localized to focal adhesion in fibroblasts and to podosomes in osteoclasts (Ory et al, 2007). We (Ory et al, 2007) and others (Chuang et al, 2007) also reported that Wrch1 regulated focal adhesion assembly and cell migration in fibroblasts and epithelial cells.…”
Section: Introductionmentioning
confidence: 99%